Treatment of Nonthrombotic Iliac Vein Lesions - Joh, Maria; Desai, Kush R. (Seminars in Interventional Radiology, 2021)
Nonthrombotic iliac vein lesions (NIVLs) most frequently result from extrinsic compression of various segments of the common or external iliac vein. Patients develop symptoms associated with chronic venous insufficiency (CVI); female patients may develop symptoms of pelvic venous disease. Given that iliac vein compression can be clinically silent, a thorough history and physical examination is mandatory to exclude other causes of a patient's symptoms. Venous duplex ultrasound, insufficiency examinations, and axial imaging are most commonly used to assess for the presence of a NIVL. Catheter venography and intravascular ultrasound (IVUS) are the mainstay for invasive assessment of NIVLs and planning prior to stent placement. IVUS in particular has become the primary modality by which NIVLs are evaluated; recent evidence has clarified the lesion threshold for stent placement, which is indicated in patients with moderate to severe symptoms. In appropriately selected patients, stent placement results in improved pain, swelling, quality of life, and, when present, healing of venous stasis ulcers. Stent patency is well preserved in the majority of cases, with a low incidence of clinically driven need for reintervention. In this article, we will discuss the clinical features, workup, endovascular management, and treatment outcomes of NIVL.
Keywords: iliac vein compression; May–Thurner syndrome; chronic venous insufficiency; venous stents; interventional radiology